PESAN QUR’ANI DARI QS. ABASA UNTUK INDONESIA (STUDI KONTEKSTUAL TAFSIR) - Moh. Rifqi Wahyudi; Lalu Muhammad Zainul Ihsan (Program Pascasarjana IIQ Jakarta, 2025)
This study is motivated by the urgency of realizing the vision of Golden Indonesia 2045, which is challenged by structural inequality, a moral crisis among the younger generation, and the weak implementation of inclusive policies. These complexities reveal a gap between the ideals of national development and social realities, thus requiring ethical and epistemological references from the Qur’an. The purpose of this research is to examine QS. ‘Abasa through a contextual interpretation approach in order to formulate a paradigm of just and inclusive development. The study employs a qualitative library research method, using QS. ‘Abasa as the primary source, classical and contemporary tafsir works, as well as modern scholarly literature as secondary sources. The findings indicate that QS. ‘Abasa contains universal messages of moral-intellectual education, social inclusion, justice, ecological ethics, and eschatological awareness, which remain relevant across time. The discussion highlights the connection of these Qur’anic values with issues of human development, food security, and national vision. The novelty of this study lies in positioning QS. ‘Abasa as a conceptual framework for national development toward Golden Indonesia 2045, with significant implications for strengthening contextual Qur’anic exegesis responsive to contemporary socio-political challenges.